ANALISIS DISPARITAS PEMBANGUNAN EKONOMI WILAYAH DI PROVINSI SULAWESI TENGGARA - Nimah Muniroh Al-Auliyah (2023)
This research was conducted to find out how the condition of regional economic development disparities in Southeast Sulawesi Province. Disparity or inequality is a problem that must be addressed, one way that can be done is to develop the potential of the region so that it can reduce the level of regional inequality. The population in this study were all regencies/cities in Southeast Sulawesi Province. Sampling used a saturated sampling technique with 17 districts/cities from 2014 to 2021, so the total sample in this study was 119 data. The data used is secondary data obtained from the Central Bureau of Statistics of Indonesia and Southeast Sulawesi. To find out the level of regional inequality, analytical techniques can be used, namely the Williamson Index and Klassen Typology. Meanwhile, to determine the potential of the region, it can be seen by conducting Shift-Share Analysis and Location Quotient. The results of this study indicate that the level of inequality in Southeast Sulawesi Province is at a moderate level according to the Williamson Index approach, this is evidenced by the large number of districts/cities that fall into quadrant 4 or are classified as underdeveloped areas. Meanwhile, based on the regional potential analysis, it is known that there are 7 potential sectors in Southeast Sulawesi Province that can be developed to reduce the level of inequality. These sectors are the Agriculture, Forestry and Fisheries Sector; Mining and Quarrying Sector; Sector Water supply, Waste Management, Waste and Recycling; Construction Sector; Transportation and Warehousing Sector; Government Administration, Defense and Compulsory Social Security Sector; and the Education Services Sector.